2011
DOI: 10.1021/am101149p
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature, Shear-Induced Tribofilm Formation from Dimethyl Disulfide on Copper

Abstract: The frictional properties of a sliding copper-copper interface exposed to dimethyl disulfide (DMDS) are measured in UHV under conditions at which the interfacial temperature rise is <1 K. A significant reduction in friction is found from the clean-surface values and sulfur is found on the surface and below the surface in the wear scar region by Auger spectroscopy. Because the interfacial temperature rise under the experimental conditions used to measure friction is very small, tribofilm formation is not therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…The experiment was initiated by rst rubbing the clean copper surface for $70 cycles. 61 This created an initial wear track (about 100 mm wide) and resulted in a runin period during which the friction decreased from an initial value of $0.8 to a lower and steady value of $0.52. Thus, any further changes in friction coefficient are due to DMDS exposure and not to any evolution in the nature of the contact.…”
Section: Ambient-temperature Tribochemistry Of Dimethyl Disulfide On mentioning
confidence: 99%
“…The experiment was initiated by rst rubbing the clean copper surface for $70 cycles. 61 This created an initial wear track (about 100 mm wide) and resulted in a runin period during which the friction decreased from an initial value of $0.8 to a lower and steady value of $0.52. Thus, any further changes in friction coefficient are due to DMDS exposure and not to any evolution in the nature of the contact.…”
Section: Ambient-temperature Tribochemistry Of Dimethyl Disulfide On mentioning
confidence: 99%
“…51 However, recent works have shown that tribochemical reactions can take place even though the temperature raise during sliding is negligible or limited and highlighted the primary role of mechanical stresses in the activation of chemical reactions. 41,[52][53][54][55][56][57][58] Our calculations at zero-applied temperature provide a further evidence that mechanical stresses can promote chemical reactions. In particular, we show that the increased enthalpy under compression can destabilize the confined molecules and promote their dissociation.…”
Section: Discussionmentioning
confidence: 52%
“…Such temperature increase has been also proposed to produce local excitations, “magama plasma,” that decay rapidly into a local heating of the surface . However, recent works have shown that tribochemical reactions can take place even though the temperature raise during sliding is negligible or limited and highlighted the primary role of mechanical stresses in the activation of chemical reactions …”
Section: Discussionmentioning
confidence: 99%
“…The normal load of 20 N corresponding to a maximum Hertzian pressure of 1.61 GPa, sliding velocity of 0.13 m s −1 , and total sliding distance of 4800 m were applied for all tests. In this study, a stressed‐shearing effect on the tribofilm formation was mainly investigated and the influence of temperature was not considered . All the tests were performed at room temperature to simulate the cold‐start conditions of engine.…”
Section: Methodsmentioning
confidence: 99%
“…In order to clarify the intrinsic relationship between macroscopic tribological performance and graphene presence, reciprocating tribo‐wear testing was carried out using a commercial engine oil mixed with GNP. In this study, we mainly consider the stressed‐shearing effect on the tribofilm formation without much influence of temperature . The focus is on understanding the effect of GNP additions on tribological capability and resultant tribofilm formation.…”
Section: Introductionmentioning
confidence: 99%